Precision Control of Amphoteric Doping in CuxBi2Se3 Nanoplates - Ren, Huaying; Zhou, Jingxuan; Zhang, Ao; Wu, Zixi; Cai, Jin; Fu, Xiaoyang; Zhou, Jingyuan; Wan, Zhong; Zhou, Boxuan; Huang, Yu; Duan, Xiangfeng (Precision Chemistry, 2024)
Copper-doped Bi 2 Se 3 (Cu x Bi 2 Se 3 ) is of considerable interest for tailoring its electronic properties and inducing exotic charge correlations while retaining the unique Dirac surface states. However, the copper dopants in Cu x Bi 2 Se 3 display complex electronic behaviors and may function as either electron donors or acceptors depending on their concentration and atomic sites within the Bi 2 Se 3 crystal lattice. Thus, a precise understanding and control of the doping concentration and sites is of both fundamental and practical significance. Herein, we report a solution-based one-pot synthesis of Cu x Bi 2 Se 3 nanoplates with systematically tunable Cu doping concentrations and doping sites. Our studies reveal a gradual evolution from intercalative sites to substitutional sites with increasing Cu concentrations. The Cu atoms at intercalative sites function as electron donors while those at the substitutional sites function as electron acceptors, producing distinct effects on the electronic properties of the resulting materials. We further show that Cu 0.18 Bi 2 Se 3 exhibits superconducting behavior, which is not present in Bi 2 Se 3 , highlighting the essential role of Cu doping in tailoring exotic quantum properties. This study establishes an efficient methodology for precise synthesis of Cu x Bi 2 Se 3 with tailored doping concentrations, doping sites, and electronic properties.